2003
DOI: 10.1099/mic.0.26010-0
|View full text |Cite
|
Sign up to set email alerts
|

Digging deeper: uncovering genetic loci which modulate photosynthesis gene expression in Rhodobacter sphaeroides 2.4.1

Abstract: A new genetic locus was identified in Rhodobacter sphaeroides which is required for optimal synthesis of the light-harvesting spectral complexes as well as for optimal growth under anaerobic conditions with dimethyl sulfoxide (DMSO) as a terminal electron acceptor. The primary structure of the deduced osp gene product shows significant homology to the receiver domain of known response regulators common to bacterial two-component systems. However, site-directed mutagenesis revealed that the Osp protein appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Several of the regulatory genes show little variation in expression levels regardless of the growth conditions, e.g. osp (64), ppsR (14,65), mgpS (66), ihfA (67), ihfB (67), prrA (49), and fnrL (16). On the other hand, prrB (8,10), prrC (25), appA (50), ppaA (68), and tspO (56) reveal significant changes in expression levels, depending on growth condition.…”
Section: Effect Of Oxygen and Light On R Sphaeroides Transcriptomementioning
confidence: 99%
“…Several of the regulatory genes show little variation in expression levels regardless of the growth conditions, e.g. osp (64), ppsR (14,65), mgpS (66), ihfA (67), ihfB (67), prrA (49), and fnrL (16). On the other hand, prrB (8,10), prrC (25), appA (50), ppaA (68), and tspO (56) reveal significant changes in expression levels, depending on growth condition.…”
Section: Effect Of Oxygen and Light On R Sphaeroides Transcriptomementioning
confidence: 99%
“…The genes of unknown function (RSP0293-RSP0295), which are located in the vicinity of the large PS gene cluster, also showed the same class II-2 expression pattern, suggesting a relationship to PS gene expression, which remains to be tested. Other photosynthesisrelated genes that showed the class II-2 expression pattern were cycA (RSP0296), encoding cytochrome c 2 , which is an electron carrier for the PS reaction center (20); pucC (RSP0315), which is involved in LHII assembly; osp (RSP0869), which is required for optimal synthesis of spectral complexes, as well as for optimal growth under dark-dimethyl sulfoxide conditions (59); blrB (RSP1261), a blue-light receptor of the BLUF family; prrA (RSP1518), a response regulator involved in oxygen regulation of the photosynthesis genes (24); the second LHII genes pucBA2 (RSP1556-RSP1557) (87); and appA (RSP1565), an antirepressor of PpsR (25). dxsA (RSP0254), which is located downstream of the puf genes, is also in this class.…”
Section: Figmentioning
confidence: 99%
“…The absence of these conserved residues suggest that this protein is not phosphorylated. In this regard, it was previously observed that in R. sphaeroides 2.4.1 the mutant version Osp D51A promoted the expression of the photosynthetic genes as wild-type Osp did ( 32 ).…”
Section: Resultsmentioning
confidence: 93%
“…We learned that the RSWS8N_09785 homologous gene in R. sphaeroides 2.4.1 was previously reported to be a positive regulator of photosynthesis but in that report, no relationship with the TCS CckA/ChpT/CtrA was established. This gene was named osp that stands for optimal synthesis of the photosynthetic apparatus ( 32 ).…”
Section: Resultsmentioning
confidence: 99%